2018
DOI: 10.24126/jobrc.2018.12.1.553
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Genotoxicity Enhancement of the Antileukemic Drug 6-Mercaptopurin When Combined With Iraqi Nerium oleander and Narcissus tazetta Extracts in vivo

Abstract: The present study was aimed to evaluate the genotoxicity of the aqueous extracts of Nerium oleander leaves and Narcissus tazetta bulbs each alone and together with the antileukemic drug 6-Mercaptopurin (6MP) in order to investigate the extracts ability to elevate the chemotherapeutic drug genotoxicity which may influence its treatment of cancer.  The cytotoxicity test shows that the LD50 of the aqueous extract of Narcissus tazetta was 752.083 mg/kg and for Nerium oleander was 922.023 mg/kg. On the basis of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The bulbs of Narcissus tazetta are rich in different biologically active components, as chemical analysis revealed, and these results were approved by other studies [27]. It was shown that 80% ethanolic solution was a good solvent for total phenolic extraction and yielded an amount greater than the total flavonoid content in bulbs.…”
Section: Discussionmentioning
confidence: 73%
“…The bulbs of Narcissus tazetta are rich in different biologically active components, as chemical analysis revealed, and these results were approved by other studies [27]. It was shown that 80% ethanolic solution was a good solvent for total phenolic extraction and yielded an amount greater than the total flavonoid content in bulbs.…”
Section: Discussionmentioning
confidence: 73%
“…Our finding that concentrations equal to or higher than those inducing the LD 50 possess a well-marked genotoxic and DNA-damaging capacity expands the current knowledge of the spectrum of damage induced by natural products from narcissus plants -toxic at high doses [14], cytotoxic [15], clastogenic [16], cell cycle arrest and gene expression blocking. These effects are commonly related to the high alkaloid content.…”
mentioning
confidence: 54%
“…The HPLC chromatogram for alkaloids in the four extracted layer from plant bulbs were represented in the figures (3) and table (3) in respect with standard alkaloid "Glanthamine" Three layers appeared to contain Glanthamine alkaloid. Layers 1 and 3 were superior in containing the largest amount of the alkaloid mentioned A few studies on the natural compounds present in the narcissus plant grown in Iraq and its biological activity against microbes, infections or various diseases had been conducted (19) . The phytochemical constituents and their concentration for this plant was employed in the current study differ from what is found in Bati and co. study (20)…”
Section: Hplc Analysis Results For Standards and The Extracted Phenol...mentioning
confidence: 99%